Rancang Bangun Jemuran Otomatis Berbasis Sensor Water Drop dilengkapi Panel Surya 10 WP - Kusumo, Bayu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The design of an Automatic Clothesline Based on a Water Drop Sensor Equipped with a 10 Wp Solar Panel is designed to make household work easier in terms of drying clothes at the household level in terms of providing/availability of clean clothes every day. The components are assembled to test the motion sensor, test the battery capacity, then test the current and voltage on the solar panel. Testing of solar module characteristics is carried out based on real operating conditions (Real Operation Condition) tests by measuring the variables solar radiation (SR), temperature (S), short circuit current (Isc), open circuit voltage (Voc) of the module. The battery charging process uses a 10 Wp solar panel with a battery capacity of 9 volts / 2Ah. The testing process is carried out on Saturday-Sunday 25 – 26 May 2023 starting from 09:00 WIB to 15:00 WIB by measuring the incoming voltage once an hour to the battery. Testing is carried out using a voltmeter. The power produced by the Solar Panel without load on March 3 2023 was 8.82 Watts, and on March 4 2023 it was 7.64 Watts. The current generated during the battery charging process using solar panels on March 25 2023 was 1.08 Ampere and on March 26 2023 it was 0.09 Ampere. The power absorbed when the tool is working is 4.48 Watts. The maximum load that can be drawn is 920 grams, at a voltage of 7.7 Volts and a current of 0.70 Amperes, so the power required is 5.39 Watts